Contribuição à identificação da competência científica de um Instituto Público de Pesquisa por meio de indicadores bibliométricos - Torres, Marcela de Fátima Nascimento de Macedo (Universidade Federal de São Carlos, 2018)
In order to develop its role of carrying out scientific research and technological development in the National System of Science, Technology and Innovation (NSSTI), and to train personnel at the postgraduate level in the National Post-graduate System (NPGS), Public Research Institutes need develop and maintain differentiated scientific competences in their occupation areas. According concept elaborated in this study, scientific competence is the ability of the Public Research Institute to maintain a high performance in the execution of actions related to institutional mission by field of knowledge. Considering the characteristics of the scientific community which their researchers belong, especially in relation to the evaluation mechanisms of science and the appropriation of the competencies approach in organizational strategies, the general objective of this study was to prove the proposed thesis that it is possible to contribute to the identification of the scientific competences of Public Research Institutes through bibliometric indicators developed from databases of public access. The specific objectives included the proposal and the application of a model for the construction of indicators on training of researchers, scientific production and training of postgraduate personnel. The model was applied at the National Institute and Research of the Amazon (INPA), a Public Research Institute of the Ministry of Science, Technology, Innovation and Communications (MCTIC). The techniques of analysis involved bibliometrics, bibliometric mapping, and academic genealogy; and the tools used were scriptLattes and syncLattes to extract data from Curriculo Lattes, genealogiaLattes for information about postgraduate, VOSViewer to generate bibliometric maps, and VantagePoint® and Excel® for data processing. The fields of knowledge was standardized based on the CNPq classification system. As a result, it was found that the fields of knowledge that present high performance in the actions related to the institutional mission of generating and disseminating knowledge and training personnel for the development of the Amazon were the same. The conclusion of the study is that the scientific competence of INPA includes the areas of Ecology and Zoology, proving the proposed thesis, since it was possible to reach this conclusion through indicators elaborated from databases of public access. Forest Resources and Forestry Engineering, Botany and Agronomy are areas that perform well and cam also be considered in the Scientific competence of the Institute. Although the model is dynamic and under construction, what has been instrumentalized so far was enough to prove the proposed thesis, requiring only validation by INPA.
Contribution to the identification of the scientific competence of a Public Research Institute through bibliometric indicators
Keywords: Competência científica; Abordagem das competências; Indicadores de ciência e tecnologia; Institutos Públicos de Pesquisa; Scientific competence; Competence approach; Science and technology indicators; Public Research Institutes; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::PLANEJAMENTO EM CIENCIA E TECNOLOGIA; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA::METODOS QUANTITATIVOS. BIBLIOMETRIA